The Implementation of Partial Roya on the Settlement of Deposit Rights - Nada, Septidya Nauvalin; Setyawati, Setyawati (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
On the one hand the Regulation of the State Minister for Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 provides a solution to the practice of partial roya, but on the other hand the Regulation of the State Minister for Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 is contrary to the provisions of Article 2 paragraph (1) Act No. 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land. The problems in this study can be formulated as follows: 1) How is the partial roya regulated in the Act No. 4 of 1996 concerning Mortgage Rights?, 2) Obstacles and solutions in the implementation of partial roya towards the settlement of Mortgage Rights in the city of Semarang? This research uses an empirical legal research approach based on field research or primary data research. The specification of the research used is analytical descriptive in nature, namely describing legal symptoms, systematically describing factually and accurately and analytically, namely by providing an assessment of the results of the description without intending to provide general conclusions. The results of the research and discussion show that the partial roya arrangement is in Article 2 and Article 22 of the Act No. 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land. Obstacles and Solutions in the implementation of partial royalties for the settlement of Mortgage Rights in Semarang City, namely: 1) Banks are slow in providing a statement of settlement or roya letters, 2) The debtor does not immediately register the Mortgage (roya) registration, 3) Services at the Land Office The slow city of Semarang. Keywords: Mortgage; Partial; Redemption; Roya.